The new customer experience management : why and how the companies of the future address their customers' needs proactively - Yorgov, Ivaylo (New York, NY : Routledge, 2023)
"A comprehensive guide to a burgeoning field, this book shows how to design and implement a future-proof post-sales service program focused on proactively addressing customers' needs in a personalized way. For too long, companies have detached from customers after the moment of purchase and done post-sales service in a way that is reactive, generic, and not scalable. Empowered by the boom in data availability and analytics, future-ready companies will offer their customers proactive personalized post-sales service, and reap tangible benefits including higher customer satisfaction and retention, and less negative word of mouth - leading to increased sales and customer lifetime value. As the stories in this book demonstrate, companies like Amazon, Adobe, Garmin, and Liberty Global are leading the way, but companies do not have to be global giants to capitalize on the techniques presented in this guide. To excel at customer experience (CX) management, companies need to implement the best customer feedback and data collection and management practices, develop state-of-the-art analytical models, and have the willingness to act. This book's strong vision and actionable roadmap, illustrated with real-life success stories, make this a compelling read for CX and customer analytics leaders, practitioners, and students alike"--
OCLC-licensed vendor bibliographic record.
Keywords: Customer services; Customer relations -- Management; Selling; BUSINESS & ECONOMICS / Customer Service; BUSINESS & ECONOMICS / Marketing / General